2014
DOI: 10.1038/nature13738
|View full text |Cite
|
Sign up to set email alerts
|

Members of the human gut microbiota involved in recovery from Vibrio cholerae infection

Abstract: Given the global burden of diarrheal diseases1, it is important to understand how members of the gut microbiota affect the risk for, course of, and recovery from disease in children and adults. The acute, voluminous diarrhea caused by Vibrio cholerae represents a dramatic example of enteropathogen invasion and gut microbial community disruption. We have conducted a detailed time-series metagenomic study of fecal microbiota collected during the acute diarrheal and recovery phases of cholera in a cohort of Bangl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
355
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 343 publications
(370 citation statements)
references
References 39 publications
10
355
0
5
Order By: Relevance
“…There is also interest in enhancing quorum-sensing-controlled behaviors in beneficial bacteria. For example, bacterial biofilm formation is essential in wastewater treatment and food processing, and, in the context of the microbiome, commensal bacteria play roles in fending off invading pathogens, presumably by relying on quorum-sensing-controlled traits 12,13 . Indeed, anti- and pro-quorum-sensing compounds have been developed and show promise in relevant model systems 1417 .…”
Section: Introductionmentioning
confidence: 99%
“…There is also interest in enhancing quorum-sensing-controlled behaviors in beneficial bacteria. For example, bacterial biofilm formation is essential in wastewater treatment and food processing, and, in the context of the microbiome, commensal bacteria play roles in fending off invading pathogens, presumably by relying on quorum-sensing-controlled traits 12,13 . Indeed, anti- and pro-quorum-sensing compounds have been developed and show promise in relevant model systems 1417 .…”
Section: Introductionmentioning
confidence: 99%
“…Humans Administration of SCFAs, LED209, tempol, AI-2, CAI-1 [18,19,26,[49][50][51][52][53]61] Treat or prevent disorders and diseases e.g. metabolic syndrome, obesity and cholera…”
Section: Signalling Moleculesmentioning
confidence: 99%
“…Humans Engineered microbes that overexpress quorum sensing molecules [49][50][51][52] Treat bacterial infection and dysbiosis…”
Section: Synthetic Biologymentioning
confidence: 99%
“…In Malawi, Gordon has shown that children with a protein deficiency disorder, called kwashiorkor, have a different type of gut community than their unaffected twin siblings (1). In Bangladesh, Gordon has identified a set of bacterial species associated with both healthy growth in children (2) and recovery from cholera in adults (3). Gordon has other ongoing research projects in India, Peru, South Africa, and Brazil.…”
mentioning
confidence: 99%
“…Much of Gordon's research also involves transplanting human microbes into germfree mice for further analysis. By transplanting a community indicative of a healthy gut in Bangladeshi children, the researchers revealed a bacterial pathway that helps the gut ward off infections (3).…”
mentioning
confidence: 99%